A new distributed charge approach for the electric vehicle parking lots considering coordination between DSO and EV operators - Gokcek, Tayfur; Boynuegri, Ali Rifat; Guner, Sitki; Erdinc, Ozan; Sadreddini, Jale (ELSEVIER SCI LTD, 2025)
The proliferation of electric vehicles (EVs) causes a series of significant operational challenges for distribution system operators (DSOs) such as voltage control and power losses. This paper proposes a novel optimal charge scheduling method that balances the interests of both the DSO and the EV parking lot (EVPL) operator. Within the coordinated framework of Alternating Direction Method of Multipliers based distributed solution, the DSO aims to maximize the load factor, while the EVPL operator seeks to minimize charging costs. The proposed method avoids peak loading caused by the EVPL during low price time intervals, while it prevents the higher operation costs due to the high price time intervals caused by the DSO's day ahead pricing scheme. Furthermore, the presented optimization model is experimentally tested for the individual operations, and coordinated operation.
Keywords: Distributed optimization; Distribution system operator; Electric vehicles; Experimental verification; Load factor; DISTRIBUTION NETWORKS; DISTRIBUTION-SYSTEM; MULTIAGENT SYSTEM; ALGORITHM; STRATEGY; DEMAND; Energy & Fuels; Engineering